Out of family, into history: A comparative study of the superchild in Corriere dei Piccoli, TBO and The Adventures of Tintin. Issue 1 (1st November 2021) - Pintor Iranzo, Ivan; Van de Wiele, Eva
Through the sagacious insights of Jean-Marie Apostolidès about Hergé's well-known character Tintin, this article gathers a comparative investigation on the relationship between the child and the absence of family. More specifically, we address the figure defined by Apostolidès as 'superchild' through a comparison between the publications Corriere dei Piccoli(CdP), in Italy, TBO, in Spain and, in the Belgian case, of the figure that motivated the term used by Apostolidès, Tintin. The article forms a comparative comics exercise from a hermeneutical-historical, narratological methodology linked to the figural study of images (Brenez 1998; Bellour 2013), in order to underline some of the singularities of the bond between the superchild and the absent family.